Metabolic patterns of new psychoactive substances: Methyl-ketamine and 2-oxo-PCE in rats using UHPLC-QTOF analysis - Yu-gang Cai; Yan-jun Wang; Yong-fu Wu; Jia-yi Feng; Yan Mo; Qing-hong Wang; Yong Dai (Forensic Science International: Synergy, 2025)
This study investigated the metabolic profiles of two isomeric psychoactive agents, methyl-ketamine [2-(ortho-tolyl)-2-(methylamino)cyclohexanone] and 2-oxo-PCE [2-(phenyl)-2-(ethylamino)cyclohexanone], in rats. Following oral administration, blood, liver, and urine samples were collected at timed intervals and analyzed via ultrahigh performance liquid chromatography quadrupole time-of-flight mass spectrometry (UHPLC-QTOF-MS). Metabolomic comparisons revealed distinct metabolic pathways driven by structural differences. Methyl-ketamine primarily underwent cyclohexanone hydroxylation, dehydration, N-demethylation, cyclohexanone carbonyl hydrogenation, and glucuronidation, with N-dealkylation as the dominant process. In contrast, 2-oxo-PCE metabolism involved carbonyl hydrogenation of cyclohexanone, N-diethylation, deamination, hydroxylation, dehydration, and glucuronidation. Structural variations—specifically the steric hindrance imposed by the methyl group on o-tolyl in methyl-ketamine—were identified as key factors influencing metabolic divergence. This hindered the carbonyl hydrogenation of cyclohexanone observed in 2-oxo-PCE, while promoting hydroxylation/dehydration reactions in methyl-ketamine. Post-N-dealkylation, methyl-ketamine retained cyclohexyl hydroxylation/dehydration, whereas 2-oxo-PCE exhibited deamination and cyclohexanone carbonyl hydrogenation/dehydration. Notably, urinary metabolite profiles in humans were mirrored those in rats, and relevance was shown. It was elucidated how structural isomerism dictating metabolic outcomes and offering insights into the mechanistic basis of new psychoactive substances. The study underscored steric effects as critical determinants of metabolic pathways and provided a foundation for predicting pharmacokinetic behavior in related compounds.